A Linguistic Analysis of Satire in Ubayd Zakani’s Works and Its Comparison with Modern Satire in Sadegh Hedayat’s Writings - Ahmadian, Seyedeh Zahra; Faraji, Mahdi (Treasury of Persian Language and Literature, 2025)
Satire in Persian literature has long served as a tool for social and cultural critique. This study conducts a linguistic analysis of satire in Ubayd Zakani’s works and compares it with modern satire in Sadegh Hedayat’s writings. Zakani employs simple language and narrative storytelling to critique social corruption in his era, while Hedayat uses a more complex language and psychological allegories to address issues in modern society. The findings reveal that despite stylistic and temporal differences, both authors utilize satire effectively to reflect social and psychological realities, showcasing its enduring relevance in Persian literature.